2021
DOI: 10.3390/cancers13081761
|View full text |Cite
|
Sign up to set email alerts
|

Digital Gene Expression Analysis of Epithelioid and Sarcomatoid Mesothelioma Reveals Differences in Immunogenicity

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive malignancy associated with asbestos exposure. Median survival ranges from 14 to 20 months after initial diagnosis. As of November 2020, the FDA approved a combination of immune checkpoint inhibitors after promising intermediate results. Nonetheless, responses remain unsatisfying. Adequate patient stratification to improve response rates is still lacking. This retrospective study analyzed formalin fixed paraffin embedded specimens from a cohort of 22 MPM. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…A much stronger effect was observed after the usage of CM from IMR-90 in comparison to those from MRC-5. In a previous study, we were able to identify that cell–cell interaction via cytokines seems to be of greater importance in patients with an epithelioid subtype of MPM [ 27 ]. These results are consistent with our in vitro observation in this study since most of significant changes in phosphorylation pattern also occurred in the epithelioid NCI-H2052 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…A much stronger effect was observed after the usage of CM from IMR-90 in comparison to those from MRC-5. In a previous study, we were able to identify that cell–cell interaction via cytokines seems to be of greater importance in patients with an epithelioid subtype of MPM [ 27 ]. These results are consistent with our in vitro observation in this study since most of significant changes in phosphorylation pattern also occurred in the epithelioid NCI-H2052 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Factorial normalization as well as biological normalization were performed with the geometric mean for all reference genes, as described in a previous study [50].…”
Section: Nanostring Data Processing and Statistical Analysismentioning
confidence: 99%
“…For statistical analysis, several tests were carried out prior to exploratory data analysis: Shapiro-Wilks test; Wilcoxon Mann-Whitney rank sum test or a two-sided Student's ttest; Kruskal-Wallis test or ANOVA; Fisher's exact test; Pearson's Chi-squared test and Spearman's rank correlation and Pearson's product-moment correlation were performed, as described elsewhere [50].…”
Section: Nanostring Data Processing and Statistical Analysismentioning
confidence: 99%
“…The involvement of the immune system is crucial in MM development and progression, however, as MM consists of different histological subtypes varying in aggressiveness, an important understanding of the biological background of its escape mechanisms was provided by Brcic, Mathilakathu et al [ 12 ]. With the development of immune checkpoint therapy, Kitajima et al also demonstrated how hybrid imaging modalities could contribute to therapy response assessment and predict prognosis [ 13 ].…”
mentioning
confidence: 99%